The Influence of The United Nations in Decision-Making Regarding The Israel-Palestine Conflict: A Literature Study - Mochamad Hanif Makarim; Atiila Maulana Saputra; Galang Putera Pangestu; Holis Ukasyah; Naufal Arief Budiman; Nayla Bunga Safa Felisa; Jaliludin Muslim (Pen of Social Science, 2026)
This study examines the influence of the United States on United Nations decision-making processes regarding the Israel–Palestine conflict through a literature review approach. As a permanent member of the UN Security Council, the United States holds veto power that grants structural authority to block resolutions even when supported by the majority of member states. This research identifies three main dimensions of such influence: (1) the consistent use of veto power to obstruct resolutions unfavorable to Israel, including vetoing three ceasefire resolutions in the first six months of the Gaza war after October 2023; (2) the impact of pro-Israel lobbying on U.S. domestic politics, particularly through organizations such as AIPAC, which systematically shapes American foreign policy in multilateral forums; and (3) informal mechanisms including diplomacy and political pressure on other member states. The consequences of this veto pattern are significant: UN resolutions frequently fail to pass despite majority support, international sanction mechanisms cannot function optimally, and the credibility of the UN as a global peacekeeping institution is further eroded. These findings indicate that UN decision-making is not neutral, but is shaped by an unequal distribution of power within the international system, consistent with the realist perspective in international relations.